2011
DOI: 10.1111/j.1439-0396.2010.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Ileal digestibility of amino acids, phosphorus, phytate and energy in pigs fed sorghum-based diets supplemented with phytase and Pancreatin®

Abstract: The effects of phytase supplementation on the apparent ileal digestibility (AID) of amino acids (AA) have been inconsistent. Two experiments evaluated the effect of providing a mixture of pancreatic enzymes (Pancreatin(®) ) to growing pigs fed sorghum-soybean meal diets supplemented with phytase on the AID of AA, energy, and phosphorus (P), as well as the ileal digestibility (ID) of phytate; there were four periods per experiment. In Experiment 1, eight pigs (BW 22.1±1.3 kg) were fitted with a T-cannula at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…This is in agreement with a study on poultry, in which the addition of a phytase product (RONOZYME HiPhos) at 5000 U/g to the diets (at 0.04%) containing different protein sources (soybean meal, yellow lupin meal, and blue lupin meal) did not affect the ATTD of the protein [16]. Similarly, Cervantes et al [26] conducted a study on swine fed with sorghum-soybean meal diets supplemented with phytase and observed no improvement in the ATTD of amino acids. Zeng et al [27] found that the ATTD of crude protein was significantly increased in piglets (20-25 kg) fed a diet with 0.14% non-phytate-P and 0.38% total P only at a concentration of 20,000 FTU/kg and not at 500 or 1000 FTU/kg.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with a study on poultry, in which the addition of a phytase product (RONOZYME HiPhos) at 5000 U/g to the diets (at 0.04%) containing different protein sources (soybean meal, yellow lupin meal, and blue lupin meal) did not affect the ATTD of the protein [16]. Similarly, Cervantes et al [26] conducted a study on swine fed with sorghum-soybean meal diets supplemented with phytase and observed no improvement in the ATTD of amino acids. Zeng et al [27] found that the ATTD of crude protein was significantly increased in piglets (20-25 kg) fed a diet with 0.14% non-phytate-P and 0.38% total P only at a concentration of 20,000 FTU/kg and not at 500 or 1000 FTU/kg.…”
Section: Discussionsupporting
confidence: 91%
“…However, the effects of phytase supplementation on AA and CP digestibility have not been consistent. For example, studies by Liao et al (2005), Woyengo et al (2008) and Cervantes et al (2011) found no significant effects due to phytase supplementation. In the present study, there was an interaction of pea cultivar and phytase in some AA, because phytase supplementation increased AA digestibility in NPP and the specific AA were: Ile, met, Phe, Val, Ala, Asp, Gly, Pro and Ser.…”
Section: Discussionmentioning
confidence: 94%
“…To minimize the effects of phytate, dietary supplementation with phytase has been successfully used to improve P digestibility in pigs (Harper et al, 1997;Woyengo et al, 2009). However, the effect of phytase supplementation on AA and energy digestibility is variable (Sands et al, 2009;Kiarie et al, 2010;Cervantes et al, 2011;Selle et al, 2012;Woyengo and Nyachoti, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Champagne et al (1990) suggested that ternary protein-phytate complexes may not have the capacity to bind sufficient protein to be important in respect of AA digestibility, due to reason that protein would be mainly present as lower molecular weight peptides. This might explain the lack of effect of phytase on protein digestibility in several studies (N€ asi et al, 1995;Traylor et al, 2001;Cervantes et al, 2011).…”
Section: Phytate-protein Interactionsmentioning
confidence: 98%
“…Trypsin is the most critical pancreatic protease, because it autocatalysis its activation and subsequently activates the other proteases. Cervantes et al (2011) suggested that if the activity of pancreatic proteases is reduced by phytates, the application of exogenous pancreatic enzymes including trypsin would overcome this effect. However, they did not find any effect on the AID of protein or AA.…”
Section: Phytate-protein Interactionsmentioning
confidence: 99%